Peningkatan Kemampuan Pemecahan Masalah Matematis Siswa Kelas VII di MTs Ath-Thohiriyah dengan Menggunakan Model Pembelajaran Kooperatif Tipe STAD - Rahmawati, Astri; Faturohman, Ikhsan; Sahadah, Ina; Sa'baniah, Sufi Nur; Aprilia, Hilda; Awaliya, Siti Nazatul (Papanda, 2025)
This study aims to determine the effectiveness of the implementation of the Student Teams Achievement Division (STAD) Cooperative Learning Model in improving students' mathematical problem solving skills. The method used is quantitative research with a pre-experimental one group pretest-posttest design. The sampling technique used purposive sampling, namely selecting 25 students from class VII of MTs Ath-Thohiriyah, selected based on the mathematics teacher’s consideration that the class had heterogeneous abilities and was conducive to implementing the new learning model. The data analysis technique used descriptive statistics (mean,median,mode,standard deviatio, minimum and maximum values) and inferential statistics in the form of the Shapiro-Wilk normality test and paired sample t-test to see significant differences between the pretest and posttest. In addition, the N-Gain Score was also calculated to measure the magnitude of the increase and its category. The results of the study showed an increase in the mathematical problem-solving ability of seventh-grade students at MTs Ath-Thohiriyah after the implementation of the STAD type cooperative learning model.